Relationship Between Gastroesophageal Reflux Disease And Type 2 Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2023)
Gastroesophageal reflux disease (GERD) has increased in prevalence over the past 20 years worldwide. Also, diabetes mellitus (DM) is becoming increasingly common in the general population. DM and GERD have a two-way association effect on health. Both conditions have had a significant negative impact on the cost of healthcare and have even impeded societal and economic growth. A Literature review in the field provides conflicting information regarding the prevalence of GERD in diabetes individuals. Studies have been performed recently to assess the relationship between GERD and type 2 diabetes. Some studies revealed a positive association between type 2 diabetes and GERD, while others found no association between these conditions.